A phase 1b study of once‐weekly carfilzomib combined with lenalidomide and dexamethasone in patients with newly diagnosed multiple myeloma. Issue 2 (15th December 2020) - Alsina, Melissa; Landgren, Ola; Raje, Noopur; Niesvizky, Ruben; Bensinger, William I.; Berdeja, Jesus G.; Kovacsovics, Tibor; Vesole, David H.; Fang, Belle; Kimball, Amy S.; Siegel, David S.
Abstract: Twice‐weekly carfilzomib with lenalidomide‐dexamethasone (Rd) is an effective regimen for newly diagnosed multiple myeloma (NDMM). Here we evaluated once‐weekly carfilzomib with Rd (once‐weekly KRd) in NDMM patients. The NDMM patients were enrolled regardless of transplant eligibility. Patients received carfilzomib on days 1, 8, and 15; lenalidomide 25 mg on days 1‐21; and dexamethasone 40 mg on carfilzomib days (also day 22 for cycles 1‐8) for ≤18, 28‐day cycles. Enrollment initiated in a carfilzomib 20/70 mg/m 2 (20 mg/m 2 on cycle one, day 1; 70 mg/m 2 thereafter) NDMM dose‐expansion arm, which was suspended because of serious adverse events. After evaluation of dose‐limiting toxicities in a two‐step‐up dose‐evaluation cohort, an NDMM dose‐expansion arm (carfilzomib 20/56 mg/m 2 ) was opened. Fifty‐one NDMM patients were enrolled in dose‐finding and dose‐expansion cohorts. Results are presented for the carfilzomib 56 mg/m 2 NDMM dose‐expansion arm (n = 33). The grade ≥ 3 treatment‐emergent AE (TEAE) rate was 63.6%. Twenty‐five patients underwent stem cell collection; 18 proceeded to auto stem cell transplant, and five resumed KRd on study after autoSCT. The overall response rate (ORR) based on best overall response by cycle four was 97.0% (≥very good partial response [VGPR], 69.7%) in the NDMM 20/56 mg/m 2 cohort. In patients who did not receive autoSCT (n = 15), the median number of cycles was 16.0; ORR was 93.3% (≥VGPR, 80.0%). At a median follow‐up of 8.1 months, median progression‐free survival was not reached. Once‐weekly KRd (carfilzomib 56 mg/m 2 ) had a favorable safety profile and promising activity in NDMM, supporting the use of this regimen in this setting.